Validitas media game edukasi berbasis Wordwall pada pembelajaran Bahasa Indonesia kelas II SD - Evie Nur Fadila; Ina Agustin; sri Cacik (Universitas Islam Nahdlatul Ulama Jepara, 2026)
This research was motivated by the limited use of interactive learning media in Indonesian language learning for second-grade elementary school students, resulting in low student engagement during classroom activities. This study aimed to determine the validity of a Wordwall-based educational game for Indonesian language learning in second-grade elementary school. The study employed the Research and Development (R&D) method using the ADDIE development model, limited to the Development stage. The research instruments consisted of validation sheets completed by material, media, and language experts. Data were collected through observation, interviews, and validation questionnaires. Pre-test results showed that all students had not achieved the Minimum Learning Achievement Criteria (KKTP), with an average achievement score of 57.4%, indicating the need for more interactive learning media. The validation results showed that the educational game obtained scores of 84% from the material expert, 100% from the media expert, and 90% from the language expert, with an average validity of 91.3%, categorized as highly valid. Therefore, the developed Wordwall-based educational game is highly valid and feasible for use as an interactive learning medium in Indonesian language learning for second-grade elementary school students.